2019
DOI: 10.1051/e3sconf/20198903004
|View full text |Cite
|
Sign up to set email alerts
|

Toward a mechanistic understanding of wettability alteration in reservoir rocks using silica nanoparticles

Abstract: Traditional concepts of simple liquid spreading may not apply to nanoparticle-fluids. Most investigations pertaining to the wettability alteration of solid surfaces due to the presence of nanoparticles in the fluid are oversimplified, i.e. nanoparticles dispersed in DI-water and smooth, homogeneous, and clean surfaces have been used. From a practical enhanced oil recovery (EOR) point of view, the nanoparticles must be dispersed in either seawater or high salinity formation water containing diverse types and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is worth noting that for the structural disjoining pressure mechanism to be effective for EOR, it requires a long-range force or high NP concentration [32,34]. Additionally, there should be no tendency for the NPs to adsorb on the rock surface [35], so that NPs can confine themselves in a pre-existing wetting-wedge [36]. Thus, it seems that the concept of structural disjoining pressure mechanism cannot be generalized to explain the wetting and oil recovery by virtue of nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that for the structural disjoining pressure mechanism to be effective for EOR, it requires a long-range force or high NP concentration [32,34]. Additionally, there should be no tendency for the NPs to adsorb on the rock surface [35], so that NPs can confine themselves in a pre-existing wetting-wedge [36]. Thus, it seems that the concept of structural disjoining pressure mechanism cannot be generalized to explain the wetting and oil recovery by virtue of nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the contact angle of the aqueous phase decreased as the nanoparticle size diminished. 123 As suggested by the disjoining pressure theory, nanoparticles can induce wettability change when a wedge film is formed at the interface between the oil, water, and rock surface. 124 As illustrated in Figure 17, the spreading and wetting of nanofluids on solid surfaces are enhanced by the nanoparticle selfassembly within the region that is inside the wedge film between an oil drop, air, and solid surface.…”
Section: Influence Of Nanoparticles On the Adsorption Reductionmentioning
confidence: 99%
“…Moreover, the performance of nanoparticles in wettability alteration is influenced by different factors, including the particle size, concentration, and salinity of the base fluid. It has been shown that the contact angle of the aqueous phase decreased as the nanoparticle size diminished …”
Section: Influence Of Chemical Structures In Fluid–fluid and Fluid–ro...mentioning
confidence: 99%